The effect of 12 weeks combined training on the antioxidant/oxidative indexes in HIV-infected patients - Abbass katanchi (فصلنامه ابن سینا)
Background: Human immunodeficiency virus (HIV) infection have been associated with high oxidative stress in HIV patients. The aim of this study was to investigate the effect of 12 weeks combined training on the antioxidant/oxidative indexes in HIV-infected patients. Materials and methods: In this semi-experimental study, 30 AIDS patients were selected in a targeted and accessible way and were randomly divided into two groups; combined training and control. The combined training program was run for 12 weeks and three sessions per week. Aerobic training involves walking or jogging on a treadmill with a rising intensity from 40% to 65% of maximum heart rate for 30 to 60 minutes. Also, Strength training includes two to four sets and 12 to 20 repetitions per isotonic device, which increased in the range from 40% to 60% 1RM. Serum Superoxide dismutase (SOD) and Malondialdehyde (MDA) levels were calculated using the ELISA method. Data were analyzed by independent and dependent t-test at the p <0.05. Results: The results showed that 12 weeks of combined training caused a significant increase in SOD level (p=0.009). Also, combined training and control conditions caused a significant decrease in MDA (p=0.001), and no significant difference was observed between the MDA levels of the two groups (p = 0.195). Conclusion: it seems that regular combined training can help to reduce oxidative damage in HIV patients.